2014
DOI: 10.1080/00288330.2014.914042
|View full text |Cite
|
Sign up to set email alerts
|

DNA identification of the phyllosoma diet ofJasus edwardsiiandScyllarussp. Z

Abstract: The development of an effective artificial larval diet has been a major stumbling block for advancing the aquaculture of spiny lobsters internationally. Attempts to determine the natural diet of spiny lobster larvae have been impeded by their small size and sparse distribution in the open ocean, making these larvae difficult to study using conventional methods. Recent advances in molecular genetic techniques have provided a novel route for identifying the natural prey of spiny lobster larvae (phyllosoma). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…These high-throughput amplicon sequencing technologies have extremely high detection sensitivity and bypass the biases posed by visual methods. Recently, the application of DNA metabarcoding to marine predator gut contents has demonstrated the capacity of these methods to detect gelatinous prey [18][19][20][21][22]. In the study of gelatinous zooplankton as consumers, this technology has only been applied to assess the microbial diet of the tunicate Salpa thompsoni [23], the predatory diet of the scyphomedusa Aurelia coerulea [24], and the diet of the lobate ctenophore Mnemiopsis leidyi [25].…”
Section: Introductionmentioning
confidence: 99%
“…These high-throughput amplicon sequencing technologies have extremely high detection sensitivity and bypass the biases posed by visual methods. Recently, the application of DNA metabarcoding to marine predator gut contents has demonstrated the capacity of these methods to detect gelatinous prey [18][19][20][21][22]. In the study of gelatinous zooplankton as consumers, this technology has only been applied to assess the microbial diet of the tunicate Salpa thompsoni [23], the predatory diet of the scyphomedusa Aurelia coerulea [24], and the diet of the lobate ctenophore Mnemiopsis leidyi [25].…”
Section: Introductionmentioning
confidence: 99%
“…This has been substantiated by captive observations of Palinurid and Scyllarid phyllosoma feeding on gelatinous zooplankton (Saunders et al., ; Wakabayashi, Sato, Hirai, & Tanaka, ), with additional evidence provided by mouth and gut morphologies that appear suited to feed on soft, fleshy foods, such as gelatinous zooplankton and detritus (Mikami, Greenwood, & Takashima, ), as well as other adaptations to resist stinging nematocysts (Kamio, Wakabayashi, Nagai, & Tanaka, ; Kamio et al., ; Wakabayashi, Nagai, & Tanaka, ). Most phyllosoma are widely thought to be generalist predators (Connell, O'Rorke, Jeffs, & Lavery, ; Jeffs, Nichols, Phleger, & Mooney, ; Saunders et al., ) and attach to medusae in a non‐selective manner (Wakabayashi, Sato, Hirai, & Tanaka, ). The two hypotheses of phyllosoma utilizing gelatinous zooplankton as transport assistants or food resources may not be mutually exclusive because there could be multiple benefits that maintain the phyllosoma‐jelly association.…”
Section: Introductionmentioning
confidence: 99%
“…The use of probiotic bacteria as additives to commercial formulated feeds were tested by Hadi et al (2014) in feeding trials of New Zealand black-footed abalone (Haliotis iris), showing positive improvements in growth rates. Using DNA sequencing techniques, Connell et al (2014) identified a range of zooplankton prey in the natural diet of phyllosoma of crayfish (Jasus edwardsii) and slipper lobster (Scyllarus sp. Z), with significant implications for future development of effective artificial diets for crustacean larvae.…”
Section: Introductionmentioning
confidence: 99%